2008
DOI: 10.2340/16501977-0276
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of functional outcome measures for the hemiparetic upper limb: A systematic review

Abstract: As yet there is no single valid and reliable outcome measure available to capture the full range of "real-life" function in the hemiparetic upper limb. Validated tools are particularly required for passive and lower level function. The selection of measures for clinical evaluation will depend on the patient's level of function and goals for treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
109
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(112 citation statements)
references
References 44 publications
0
109
0
3
Order By: Relevance
“…However, motor ability and the use of the UL in this context may not correspond to what the individuals really perform in their daily lives. Thus, it is important to rely on adequate instruments to assess relevant aspects of functional performance in real life contexts 9 . The effects of neurorehabilitation on the most affected UL use in the real world are largely unexamined, and deficits in the most affected UL use after neurological injuries may be underdiagnosed 8 .…”
mentioning
confidence: 99%
“…However, motor ability and the use of the UL in this context may not correspond to what the individuals really perform in their daily lives. Thus, it is important to rely on adequate instruments to assess relevant aspects of functional performance in real life contexts 9 . The effects of neurorehabilitation on the most affected UL use in the real world are largely unexamined, and deficits in the most affected UL use after neurological injuries may be underdiagnosed 8 .…”
mentioning
confidence: 99%
“…For example, there is currently no single valid and reliable scale available that comprehensively captures the complete range of function hemiparetic upper limb. 7 Furthermore, scales that focus on the participation component of the ICF are extremely limited. 19 Finally, the use of PRO measures in stroke research is a relatively new development 31,32 and is complicated in this population by cognitive and communication difficulties that can occur in stroke survivors.…”
Section: Discussionmentioning
confidence: 99%
“…6 Systemic reviews can help to select outcome measures. For example, Ashford et al 7 reviewed measures for the hemiparetic upper limb, identified 6 scales that met their selection criteria, but concluded that currently there was no single reliable and valid measure available to capture the full range of functional tasks in the hemiparetic upper limb. This type of systematic review provides invaluable information but also raises important questions.…”
mentioning
confidence: 99%
“…The existing measurements usually have a quantitative approach (for example measures time to perform a movement, the number of possible repetitions of a movement, and active range of motion) without identifying whether the movement is similar to premorbid movements or whether the action occurs through compensatory movements. In addition, there is a lack of standardization of passive range of motion and movement quality of active range especially when there is a low level of arm function [7].…”
Section: Introductionmentioning
confidence: 99%